(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
The aim of this experiment was to investigate the control of programmed contingencies on private events (feelings), using a procedure that caused those events and evoked the tact of them (feelings), explaining how programmed contingencies of reinforcement are linked with the tacts of private events. Twenty students (both sex aged between 11 and 14 years old) executed the assignments from the software PsychoTacto 2.0. The software simulated four basic contingencies (positive and negative reinforcement, positive and negative punishment), and at the end of each step the students told what they felt. Answers were measured. Results: In each phase predominated reports: Positive Reinforcement: contentment, anxiety, satisfaction and joy reports. Negative Punishment: frustration, disappointment, sadness and apprehension reports. Positive Punishment: anger, disgust, anxiety, apprehension and fear. Negative Reinforcement: anxiety, apprehension and relief. It follows that data indicate that the exhibition to contingencies can eliciate private events (feelings) and produce tacts of them, according to theoretical analysis of Behavior Analysis studies.